STANISŁAW KUCZERA (5 MAY 1928–28 JULY 2020). (September 2021) - Dmitriev, Sergey
Abstract: Stanisław Kuczera (May 5, 1928–July 28, 2020) was an eminent figure in Polish, Soviet, and Russian Chinese Studies, holding the position of one of leading experts in a vast number of fields (most prominently, archeology, epigraphy, and the translation of classics) over a period decades, until his last days. His life, filled with a thirst for knowledge and harsh vicissitudes, is a story that is worthy of being told and remembered.